Is Agile Cure for Everything - Agarwal, Rahul; Singh, Anurupa; Joshi, Ambrish (International Journal of Engineering and Technology, 2018)
This research paper explores Agile- more in terms of its successes, its limitations, myths around Agile and where it could be the best fit. The paper also envisions to demystify the aura around Agile methodology with excerpts gathered from discussions with some of the Agile thought leaders.